The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.13057/biodiv/d170207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of antixenosis, antibiosis, and tolerance of fourteen soybean genotypes in response to whiteflies (Bemisia tabaci)

Abstract: Sulistyo A, Inayati A. 2016. Mechanisms of antixenosis, antibiosis, and tolerance of fourteen soybean genotypes in response to whiteflies (Bemisia tabaci). Biodiversitas 17: 447-453. The attack of whiteflies (Bemisia tabaci) in soybean cultivation in Indonesia is one of the limiting factors in increasing the national soybean production. Planting resistant varieties could reduce yield losses due to the damage caused by these pests. This study was conducted to evaluate the resistance of 14 soybean genotypes to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
(22 reference statements)
0
11
0
1
Order By: Relevance
“…Organic foods with reduced pesticide exposure are increasingly demanded by health-conscious consumers throughout the world. To this end, resistant plant cultivars can be used to control herbivorous pests through antibiosis and resistance development due to toxins, antifeedants, and secondary metabolite compounds (Smith, 2005; Hesler and Dashiell, 2011; Sulistyo and Inayati, 2016). Our findings demonstrated that the tested bean cultivars accumulated different levels of secondary metabolites, which affected the nutritional indices of Egyptian cotton leafworm, suggesting the potential of host quality to affect the nutritional fitness of herbivorous insects.…”
Section: Discussionmentioning
confidence: 99%
“…Organic foods with reduced pesticide exposure are increasingly demanded by health-conscious consumers throughout the world. To this end, resistant plant cultivars can be used to control herbivorous pests through antibiosis and resistance development due to toxins, antifeedants, and secondary metabolite compounds (Smith, 2005; Hesler and Dashiell, 2011; Sulistyo and Inayati, 2016). Our findings demonstrated that the tested bean cultivars accumulated different levels of secondary metabolites, which affected the nutritional indices of Egyptian cotton leafworm, suggesting the potential of host quality to affect the nutritional fitness of herbivorous insects.…”
Section: Discussionmentioning
confidence: 99%
“…Bemisia tabaci host species come from the families Asteraceae, Malvaceae, Solanaceae, Cruciferaceae, Lamiaceae, Euphorbiaceae, Cucurbitaceae, Fabaceae, Bignoniaceae, Lythraceae and Zygophyllaceae (Mascarin et al 2013;Sulistyo and Inayati 2016;Lima et al 2017;Macfadyen et al 2018;Costa et al 2019;Li et al 2021). The host species are mostly associated with the Fabaceae family, while Bignoniaceae, Lythraceae and Zygophyllaceae only have one species each (Song et al 2014;Li et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results were in partial agreement with Gaur et al (2018) where several germplasms were screened for antixenosis and results shows that the preference and non preference soybean germplasms was based on the antixenosis mechanism of resistance. Sulistyo and Inayati (2016) performed an experiment on soybean germplasm to establish the antixenotic resistance through free-choice and no-choice assay. Similarly, Boica Junior et al (2015) reported that the largest consumption of the leaf (high MLAC) shows that the genotype is susceptible to the pest while resistance in plant creates difference in consumption by pest.…”
Section: Larval Population Per Mrlmentioning
confidence: 99%